Legal Protection on the Brand Owners for Counterfeiting Brands Traded through Electronic Transactions on Online Marketplace Platforms (E-Commerce) - Fitri, Sintia; Afni Askar , Nur; Helendian Loemnanu , Artista; Ayudhya Shantika Devi , Ni Nengah (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
The aim of this research is to determine legal protection on the brand owners for counterfeiting brands traded through electronic transactions on online marketplace platforms (E-Commerce). This research method used normative law or what is often called library research as this research utilized statutory regulations approach or other legal materials and concepts. In which research legal materials were carried out by examining library materials. The data used uses secondary data originating from scientific journals, books and other supporting references. Brand owners are afforded legal protection by the state if their brand has been registered with the Directorate General of Intellectual Property Rights and has received exclusive rights to that brand. This protection is enforced by the state. Regarding counterfeiting of brands that are bought and sold through transactions on the Online Marketplace (E-Commerce) platform, brand owners can make efforts to resolve disputes as regulated in Law Number 20 of 2006 concerning Trademarks and Geographical Indications through court (litigation) and outside court (non-litigation).